2003
DOI: 10.1017/s0012162203001361
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorders in children with active epilepsy and learning disability: comorbidity, pre- and perinatal background, and seizure characteristics

Abstract: The aim of this study was to examine the comorbidity pattern, seizure characteristics, and aetiology in a representative group of children with a combination of autism spectrum disorder (ASD), active epilepsy, and learning disability. Ninety children (47 males, 43 females; mean age 11 years 2 months, range 8 to 16 years at the time of psychiatric examination) with active epilepsy and learning disability, identified in a population-based study in Göteborg, Sweden, were subdivided into those with and those witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
3
27
0
2
Order By: Relevance
“…17 Seizure semiology and type of epilepsy were not reported in PDDNOS, whereas they were described in autistic disorder and autistic-like conditions, which in fact are different clinical entities. [10][11][12]23 The higher occurrence of epilepsy in our sample of patients with PDDNOS (35.1%) corresponds to the value range described for pervasive developmental disorders 10,11 but is greater than the epilepsy occurrence in patients with PDDNOS reported in literature (5.6% to 30.1%). [15][16][17] In contrast, no significant differences have been reported for autistic disorder.…”
Section: Discussionsupporting
confidence: 48%
“…17 Seizure semiology and type of epilepsy were not reported in PDDNOS, whereas they were described in autistic disorder and autistic-like conditions, which in fact are different clinical entities. [10][11][12]23 The higher occurrence of epilepsy in our sample of patients with PDDNOS (35.1%) corresponds to the value range described for pervasive developmental disorders 10,11 but is greater than the epilepsy occurrence in patients with PDDNOS reported in literature (5.6% to 30.1%). [15][16][17] In contrast, no significant differences have been reported for autistic disorder.…”
Section: Discussionsupporting
confidence: 48%
“…The disorders co-occur in about 30% of individuals with either ASD or epilepsy and there is a strong association between ID, autism, and epilepsy 50. Some authors have suggested specific peaks of seizure onset in children with autism: in early childhood and in adolescence, and also with continuing risks through adulthood 50. However, such peaks have not been supported in prospective longitudinal population-based studies of epilepsy in autism 121…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Behaviour problems are also common in children with CP , including neuropsychiatric disorders such as autism spectrum disorder (ASD) and attention‐deficit/hyperactivity disorder (ADHD). During the last decade, there has been growing awareness particularly of ASD being overrepresented in children with CP, reported from 3% to 16% , depending on the group studied and the methods used. In a European multicentre CP study by Delobel‐Ayoub et al, male sex, epilepsy, ID and better walking ability were associated with ASD in children with CP .…”
Section: Introductionmentioning
confidence: 99%